Gépjárműállomány struktúra átalakításának lehetséges módozatai és szerepe a Fejérvíz Zrt. működésének, hatékonyságának javításában - Király Balázs (2020)
The aim of my work is to transform the structure of vehicle fleet at FEJÉRVÍZ ZRT. to make it sustainable for the company. It is vital for the company to maintain its operation in the current political and legal environment. Even under the current financial conditions it is a must to achieve profitable management. The condition of the vehicle fleet shows a constantly worsening and ageing trend; hence it aggravates to provide the standard of the accustomed service. If the regula-tions regarding the corporate environment and scope of activity are supposed to be con-stant, this continuation of the current management may result in the termination of opera-bility. The possible changes among the employees of the management may trigger a radical change in thinking and approach, or a decision made by the proprietor may force the current senior management to reorganize the company structures in a more cost-effective way in order to maintain operation. In the near future the departments must prepare to restructure their own scope of activity within the latitude of the creation of sustainable management to completely serve the interests and purposes of the company. Each department must be able to supervise the processes, structures regarding their own area of expertise; to explore and identify prob-lems concerning operation; to formulate proposals concerning probable transformation; as well as to outline options which contribute to the common goal. The aim is to outline such an option regarding the structure of the vehicle fleet which can turn the present trends, thus makes operability profitable: while it assures that the appropriate quality of the fleet is maintained, it also reduces operating costs. The presented structural transformation improves the operational efficiency of ve-hicle fleet; in its entirety it reduces the quantity of the vehicle fleet operated by the com-pany by 36% and its operating costs by 20% with the help of adopting a budget planning procedure based on the correction of basic data. The organizational and regional division of vehicles and the operative safety of the vehicle fleet in stock is of vital importance since it influences the effective operation of all the departments of the company, its operational costs effect all the departments, it inte-grates into every corporate process. The cost savings that can be gained this way effect the cost-effective completion of every corporate operation.